Autentificación de carne y productos cárnicos procedentes de codorniz, faisán, perdiz y pintada mediante una técnica de PCR con cebadores especie-específicos - Martín de Santos, R.; González Alonso, I.; Rojas Diéguez, M. (Revista Complutense de Ciencias Veterinarias, 2008)
Polymerase chain reaction (PCR) based on oligonucleotide primers targeting the mitochondrial 12S rRNA gene has been applied to the specific identification of meats from quail (Coturnix coturnix), pheasant (Phasianus colchicus), partridge (Alectoris spp), and guinea fowl (Numida meleagris).
Keywords: Game birds; 12S rRNA gene; Polymerase chain reaction (PCR); speciesspecific primers